2017
DOI: 10.1111/lam.12734
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dynamics in anaerobic digestion reactors for treating organic urban residues during the start-up process

Abstract: This study describes the selection of relevant bacteria and archaea in anaerobic digesters inoculated with anaerobic granular sludge from a brewery wastewater treatment plant. Generally, these sludge granules are used to inoculate reactors digesting organic urban wastes. Though, it is still not clearly understood how micro-organisms respond to substrate variations during the reactor start-up process. After feeding two reactors with organic urban residues, it was found that a broader potential for cellulose deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
0
7
0
11
Order By: Relevance
“…On the last day of each tested OLR, the number of microbes was determined from fluorescence images in the inoculum and at 75, 175, and 250 days after starting the experiment (Figure 6). The mean number of microorganisms decreased from 12,761 ± 3213 cells/mm 2 in the inoculum to 7126 ± 3099 cells/mm 2 after 75 days (Figure 7) as a result of a process of selection by the substrate [31]. The number of microbes was no different at day 175 (5739 ± 1316 cells/mm 2 ) from day 75, which suggests that the rate of duplication met an equilibrium with the OLR.…”
Section: Microbiology Assessmentmentioning
confidence: 92%
“…On the last day of each tested OLR, the number of microbes was determined from fluorescence images in the inoculum and at 75, 175, and 250 days after starting the experiment (Figure 6). The mean number of microorganisms decreased from 12,761 ± 3213 cells/mm 2 in the inoculum to 7126 ± 3099 cells/mm 2 after 75 days (Figure 7) as a result of a process of selection by the substrate [31]. The number of microbes was no different at day 175 (5739 ± 1316 cells/mm 2 ) from day 75, which suggests that the rate of duplication met an equilibrium with the OLR.…”
Section: Microbiology Assessmentmentioning
confidence: 92%
“…The reactors were operated for still one more year after the last sampling time reported here, and we observed that the granules remained as a stable part of the reactors’ sludge beds, accounting for around half of the total solids (data not shown). Other studies have reported major changes in granular species inventory due to other kinds of adaptation 13 , 14 , but they did not comment on granule abundance in the reactors after completing the adaptation. Another surprising observation is that the methanogenic community that finally handled extreme ammonia levels after a year of adaptation (HA1) was more similar to the inoculum community from a process with very low ammonia (PP) than with the culture that adapted to an ammonia level that can cause moderate inhibition (LA1).…”
Section: Discussionmentioning
confidence: 94%
“…Anaerobic digestion has gained increasing interest both as an efficient way of treating wastes and as a source of renewable energy . During anaerobic digestion, bacterial communities biotransform the substrate to alcohols, CO 2 , H 2 , and volatile fatty acid (VFA) by hydrolysis and acidogenesis processes.…”
Section: Introductionmentioning
confidence: 99%